2016
DOI: 10.17795/jjcdc-24895
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites in HIV-Positive Patients Attending Ahvaz Health Centers in 2012: A Cross-Sectional Study in South of Iran

Abstract: Background: AIDS is now known as a crisis throughout the world. Gastrointestinal parasites are the main causes of infections in HIVpositive patients. Objectives: This study aimed to investigate the prevalence of intestinal parasites in HIV-positive patients who referred to Ahvaz health centers, Ahvaz, Iran in 2012. Patients and Methods: This cross-sectional study was conducted on 200 HIV-positive patients of the Ahvaz health centers who selected by convenient sampling. Patients' demographics were recorded by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…Finally, people who are living with HIV/AIDS having a history of diarrheal disease were nearly five times more likely to develop intestinal parasitic infections as compared to their counterparts (AOR: 4.79 (95%CI: 1.53, 14.99). This study finding is supported by the study conducted in France [10] and Southern Iran [12]. The possible justification might be due to the fact that diarrhea in immune-compromised patients might result in increased PLOS ONE susceptibility to infection due to loss of fluid and electrolytes.…”
Section: Plos Onesupporting
confidence: 75%
See 1 more Smart Citation
“…Finally, people who are living with HIV/AIDS having a history of diarrheal disease were nearly five times more likely to develop intestinal parasitic infections as compared to their counterparts (AOR: 4.79 (95%CI: 1.53, 14.99). This study finding is supported by the study conducted in France [10] and Southern Iran [12]. The possible justification might be due to the fact that diarrhea in immune-compromised patients might result in increased PLOS ONE susceptibility to infection due to loss of fluid and electrolytes.…”
Section: Plos Onesupporting
confidence: 75%
“…Studies conducted in different continents showed that the magnitude of intestinal parasitic infections among HIV/AIDS patients has been varied across countries. Besides, the prevalence of intestinal parasitic infections among HIV/AIDS patients was 17% in France [10], 40% in Brazil [11], 48.8% in Iran [12], and 69% in Mexico [13]. In Africa, the magnitude of IPIs among HIV/AIDS patients was 57.48% in Cameroon [14], 24.7% in Nigeria [9], 65.3% in Burkina Faso [3], and 50.9% in Kenya [15].…”
Section: Introductionmentioning
confidence: 99%
“…Blastocystis is one of the most common enteric protozoa in HIV-infected patient due to weaken immunity [19]. In this study, the detection rate of Blastocystis was 3.70% in HIV-infected patients, it was significant lower than that reported by others conducted in HIV/AIDS patients in China [5], and some developing countries, such as Ethiopia (10.6%) [20] and Iran (19.0%) [21].…”
Section: Discussioncontrasting
confidence: 53%
“…Similarly, Adarvishi et al [36] reported that B. hominis is one of the most common intestinal protozoa in HIV-infected patients due to their depressed immune system. On the other hand, the presence of the species D. dendriticum can be explained by human contact with pets such as sheep and cattle.…”
Section: Discussionmentioning
confidence: 94%